HZSM-5 supported gallium oxide catalyst for preparing ethene by oxidative dehydrogenation of ethane with carbon dioxide - XU HUALONG; SHEN ZHENHAO; QIU JIANLI; SHEN WEI; TONG TING (2010)
The invention belongs to the field of chemistry and chemical engineering technology and energy science, and relates to a class of HZSM-5 supported Ga2O3 catalysts, in particular to an HZSM-5 supported gallium oxide catalyst for preparing ethene by oxidative dehydrogenation of ethane with carbon dioxide. The catalysts provided have high activity in the reaction of preparing C2H4 through CO2 oxidation and C2H6 dehydrogenation; and compared with beta-Ga2O3 and Ga2O3/TiO2, the catalysts have good stability. HZSM-5 serving as a carrier of the catalyst is prepared by a hydrothermal synthesis method; the control of Si/Al can be realized by regulating a feed ratio; active species Ga2O3 is loaded on the carrier by a dipping method; and the reaction of preparing C2H4 through CO2 oxidation and C2H6 dehydrogenation is performed under the conditions of reaction temperature of between 450 and 700 DEG C, pressure of between 0.1 and 0.3 MPa, C2H6 concentration of between 3 and 17 percent, CO2 concentration of between 0 and 8